Vitex negundo and Euphorbia milii leaf extracts aided green synthesis of copper oxide nanostructures for effective inactivation of pathogenic bacteria - Thambidurai S.; Arumugam J.; Kandasamy M.; Balaji D.; Pugazhenthiran N.; Jothilakshmi R.; Sathish Kumar B.; Murugesan K.; Karthick Kumar S.; Muneeswaran T.; Jayakumar K.; Suresh S. (Elsevier B.V., 2024)
A facile and green route was followed to synthesize copper oxide (CuO) nanostructures using Vitex negundo and Euphorbia milii leaf extracts. Structural, elemental, chemical, spectral and morphological features of the CuO nanostructures were determined by XRD, EDS, FTIR spectroscopy, UVVis spectrophotometer and FESEM, respectively. The CuO nanostructures disclosed considerably higher antibacterial activity against selected Gram-positive and Gram-negative pathogenic bacteria over commercial antibiotic (Vancomycin). This enhanced antibacterial activity could be credited to the generation of more ROS associated with oxygen vacancy and size of the CuO nanostructures. Particularly, hierarchical CuO nanoparticles/nanorods prepared using V. negundo leaf extract exhibited the highest antibacterial activity due to their lower size range. 2023 Elsevier B.V.